Analysis on Soil Liquefaction Potential in Pangandaran Coastal Area West Java - Anida Chaerunisa; Asriana Asriana (International Conference on Coastal and Delta Areas, 2017)
Pangandaran, West Java is well known as an earthquake prone area. The impact of an earthquake in a coastal area which contains saturated sand soil is liquefaction potential. This phenomenon occurs when earthquake hits, the water pore pressure increases and the effective stress becomes nil then the soil loss its shear strength. With the objective to study the liquefaction potential in Pangandaran coastal area, this analysis was conducted. Two kinds of analysis were performed by manually calculation method and using Quake Geostudio program. Seed’s method based on safety factor as a key control to determine the liquefaction potential was used. This method requires N-SPT data. The result of the analysis showed that based on Seed method with a value acceleration of earthquake is 0,5g, FS value is 1,55. This value means that Pangandaran coastal area is not susceptible to liquefaction. From the analysis using Quake, as ground acceleration increases, pore water pressure also increases. It means the higher of ground acceleration can have liquefaction potential. Keyword : Liquefaction, Seed method, ground acceleration, Pangandaran